At the Origin of the History of Glia. (10th August 2018) - Fan, Xue; Agid, Yves
Highlights: Scientific breakthroughs and conceptual shifts that determined the history of glia in relation to that of neurons. Respective role of technical innovations and scientific interpretations in the evolution of the science of glial cells. First hypotheses on the roles of glial cells in neurotransmission, brain functions and behavior. Impact of the history of glia on the evolution of neuroscience. Abstract: The history of brain science is dominated by the study of neurons. However, there are as many glial cells as neurons in the human brain, their complexity increases during evolution, and glial cells play important roles in brain function, behavior, and neurological disorders. Although neurons and glial cells were first described at the same time in the early 19th century, why did the physiological study of glial cells only begin in the 1950s? What are the scientific breakthroughs and conceptual shifts that determined the history of glial cells in relation to that of neurons? What is the impact of the history of glia on the evolution of neuroscience? In order to answer these questions, we reconstructed the history of glial cells, from their first description until the mid-20th century, by examining the relative role of technical developments and scientific interpretations.